Creep Behavior of Near α High Temperature Ti-6.6Al-4.6Sn-4.6Zr-0.9Nb-1.0Mo-0.32Si Alloy - Yang, Dongye; Tian, Wenqi; Zhang, Xinqi; Si, Ke; Li, Jiuxiao (Frontiers in Materials, 2021)
This study focuses on the microstructure characteristics, tensile and creep properties of a near α high temperature Ti-6.6Al-4.6Sn-4.6Zr-0.9Nb-1.0Mo-0.32Si alloy. Microstructure characteristics was quantitatively investigated using optical microscopy, scanning electron microscope and transmission electron microscopy. Tensile properties were carried out at room and high temperature. Creep properties were detected under applied stresses ranging from 100 MPa to 350 MPa at 873 K-973 K, respectively. Results showed that Widmanstätten microstructure was obtained after hot forged and heat treatment. The strength decreases and the elongation rise with temperature increasing. The ultimate strength and elongation were 1010 MPa, 12% and 620 MPa, 20% at room temperature and 923 K, respectively. The steady state creep rates rise correspondingly with stress and temperature. Stress exponents are measured within the range of 3.0-3.5. Thus, the creep mechanism is diffusion controlled viscous glide of dislocation. Ti3Al precipitates are observed. The boundaries and precipitates can obstruct dislocation movement to improve the creep properties. Fracture mechanism of creep is an intergranular. The creep mechanism varied from climb of dislocation to sliding of dislocation solution.